Kryterium obszaru oddziaływania obiektu a uznanie za stronę postępowania administracyjnego - Małgorzata Ganczar (Studia Administracyjne)
The area of influence of a facility is a key criterion for determining the status of a party in administrative proceedings concerning construction projects. According to the legal definition, it includes the area where the proposed investment restricts the development or use of neighboring properties. In administrative practice and court rulings, the analysis of the impact of the investment on the surrounding area is of particular importance, taking into account, among other things, issues of shading, noise and restrictions on access to infrastructure. The problem remains too narrow definition of the area of impact by investors and its indiscriminate acceptance by administrative bodies, which leads to restrictions on the rights of neighboring property owners. The article analyzes, based on the jurisprudence of administrative courts, the consequences of narrowing the circle of parties to the proceedings and the resulting threats to the constitutional right to a court and the protection of property. It also points out the need for uniform interpretation of the law and greater reliability of administrative bodies in assessing the real impact of investments on the surroundings.